Evaluasi penggunaan obat antihipertensi pada pasien DM tipe-2 - Perdana, Dwi Agung Jaka; Nofita, Nofita (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Sarjana Farmasi Indonesia (ISFI), 2025)
Evaluation of the use of antihypertension drug in DM type-2 patients Background : Diabetes mellitus is a metabolic disease characterized by hyperglycemia. Diabetes mellitus can lead to a variety of problems, including hypertension. Pharmacological therapy for diabetes mellitus with hypertension complications is very complex, such as the use of more than one drug. This allows the treatment results we don't expect (Unrational). Purpose : This study aims to determine the pattern of prescribing and the rationale for the use of antihypertensive drugs in type-2 Diabetes Mellitus patients at the Kedaton Hospital in Bandar Lampung in 2019 with the right parameters for diagnosis, right medication, right patient, right indication, right dose, right method and duration. giving. Method : This type of research is descriptive observational, the data is done retrospectively by using the patient's medical record. Results : The results showed the highest prevalence, namely: at the age of 56-65 years (36%), female gender (70%), 21 patients with antidiabetic drugs Glibenclamide (63%), 18 patients for other drugs namely paracetamol (26%), In the antihypertensive drug, 15 patients were Captopril (45%), with monotherapy as much as 94%. Results : From the rationality analysis of the use of antihypertensive drugs in Type-2 DM patients, it was obtained: 100% correct diagnosis, 100% correct drug, 100% accurate indication, 100% correct patient, 81% correct dose, and 66% correct duration of administration. Keywords : Evaluation, Type 2 diabetes mellitus patient, Antihypertensive drugs, Rationality. Pendahuluan : Diabetes Melitus merupakan penyakit metabolik yang ditandai dengan hiperglikemia. DM dapat menyebabkan berbagai komplikasi salah satunya hipertensi. Pemberian terapi farmakologi untuk diabetes melitus dengan komplikasi hipertensi sangat kompleks, seperti penggunaan obat yang lebih dari satu. Hal ini memungkinkan terjadinya hasil pengobatan tidak kita harapkan (Tidak Rasional). Tujuan : Untuk mengetahui pola Peresepan dan Rasionalitas penggunaan obat antihipertensi pada pasien Diabetes Mellitus tipe-2 di Puskesmas Rawat Inap Kedaton Bandar Lampung pada tahun 2019 dengan parameter tepat diagnosis, tepat obat, tepat pasien, tepat indikasi, tepat dosis, tepat cara dan lama pemberian. Metode : Observasional deskriptif, data dilakukan secara retrospektif dengan menggunakan rekam medis pasien. Hasil : Menunjukkan prevalensi terbanyak yaitu: pada usia 56-65 tahun (36%), jenis kelamin Perempuan (70%), Pada obat Antidiabetik 21 pasien yaitu Glibenklamid (63%), pada obat lain 18 pasien yaitu parasetamol (26%), Pada obat Antihipertensi 15 pasien yaitu Captopril (45%), dengan monoterapi sebanyak 94%. Simpulan : Dari analisis rasionalitas penggunaan obat antihipertensi pada pasien diabetes melitus tipe-2 diperoleh tepat diagnosa 100%, tepat obat 100%, tepat indikasi 100%, tepat pasien 100%, tepat dosis 81%, dan tepat lama pemberian 66%.